The Effect of Project Method and Self-Concept on Emotional Intelligence of Children Age 5-6 Years - Lusiyah Simanjuntak; Hasanuddin Hasanuddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Emotional intelligence becomes important to be seen from an early age because it is one of the determinants of his success in the future. with this intelligence they can recognize the emotions of others but also themselves. The purpose of this study is to see how the project method and self-concept can have an effect on emotional intelligence for children aged 5-6 years. This research is a quasi-experimental. The population is 102 children from PAUD (early childhood education) and the sampling technique is using random sampling consisting of two groups (group A with 15 children as the control class and group B with 15 children as the experimental class) with the number of samples is 30 children. The research instrument used the emotional intelligence scale of early childhood and self-concept tests. Data analysis used two-way Anova. Based on this analysis and research, the results obtained: There is a significant effect of applying the project method on emotional intelligence in children aged 5-6 years with a significance value of p= 0.001 smaller than 0.05; There is a significant effect of the application of self-concept on the emotional intelligence of children aged 5-6 years with a significance value of p= 0.001 smaller than 0.05. Project methods and relevant self-concepts are carried out on children to increase emotional intelligence and of course this becomes an important capital for future research with different place settings and situations.